GAGASAN PEMIKIRAN DAN GERAKAN DAKWAH M. NATSIR DI INDONESIA - Muridan Muridan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
M. Natsir was one of the most prominent figures in religious discourse and movement in Indonesia. He was ada’wa reformer as well as a politician and a statesman.His most well known ideas were about the relationship between Islamand state, Islam and Pancasila, and his idea on da’wa. He stated that a country would be Islamic because of neither itsformal name as an Islamic state nor its Islamic state principles. The principles of the state could be generally formulated aslong as they referred to the Islamic values. Natsir also stated that the essence of Pancasila didn’t contradict with Islam; evensome parts of it went after the goals of Islam. However, it didn’t mean that Pancasila was identical with Islam. In relation toda’wa, he stated that it should be the responsibility of all Muslims, not only the responsibility of kiai or ulama. To make a da’wamovement successful, he suggested that it needed three integrated components; masjid, Islamic boarding school, andcampus.